Concentration-dependent inhibition of acetylcholinesterase by organophosphate poisoning in dogs: a biochemical and electrocardiographic study (2016)
Organophosphate poisoning (OP) is one of the most common poisonings in developing countries. In this study, twenty-four dogs in four groups of six each were used. Control group bathed with water only, group B with 16% Coumaphos (recommended), groups C and D with times 10 and 20 of 16% Coumaphos, respectively. Blood was collected from cephalic vein for biochemical assays. Electrocardiographic parameters were assessed from a Lead-II electrocardiogram. There was a significant increase (p<0.05) in total cholesterol in group B and D compared to the control. LDL-cholesterol decreased significantly (p<0.05) in all groups compared to the control. The activity of superoxide dismutase (SOD) reduced (p<0.05) significantly across all the groups and even after 36 hours of exposure. However, the activity of the glutathione peroxidase (GPx) was not affected following exposure to OP. The serum reduced glutathione (GSH) fell in a concentration dependent manner in all animals exposed to OP. Coumaphos exposure led to a significant (p<0.05) increase in serum MDA in a concentration dependent manner after 36 hours post exposure. The serum nitric oxide (NO) and MPO content increased (p<0.05) significantly following exposure to different concentrations of Coumaphos. The activity of Acetyl cholinesterase (AchE) fell significantly from the normal concentration of the OP down to the highest concentration. The activity of serum creatine phosphokinase (CK) increased (p<0.05) significantly in groups C and D compared to the control and recommended concentration. Electrocardiographic abnormalities recorded included low-voltage R-waves, first degree heart block, significant increased (p<0.05) heart rate (HR) and shortened QT interval compared to the control and recommended concentrations. Taking together, coumaphos poisoning caused an inhibition of AchE and significant potentially fatal arrrhythmais via induction of oxidative stress.